From Policy to Empowerment: The Dynamics of the Implementation of the RodanyaMasbagia Program in Magelang City - Rachmad Kristiono Dwi susilo; Rusdianto Umar; Agung Wibowo (Jurnal Pemberdayaan Masyarakat: Media Pemikiran dan Dakwah Pembangunan, 2026)
Community empowerment has become a key agenda in local governance, yet its effectiveness depends on institutional capacity and stakeholder collaboration. This study examines the implementation of the RodanyaMasbagia Community Empowerment Program, one of the twelve flagship programs of the Magelang City Government, Central Java, Indonesia. Using a qualitative case study approach, data were collected through document analysis, in-depth interviews, and focus group discussions. The findings show that the program has provided both physical and non-physical assistance and has been continuously improved over three years of implementation. However, its effectiveness remains constrained by institutional challenges. Based on George C. Edwards III's policy implementation framework, communication and disposition emerge as the main barriers. Frequent policy changes and procurement adjustments have disrupted communication, while unequal incentives have weakened stakeholders' commitment. In addition, disparities in knowledge and technical capacity, along with fragmented coordination among local institutions, have limited effective policy implementation. The study concludes that community empowerment requires not only program implementation but also adaptive governance, stronger institutional coordination, and capacity development to achieve sustainable outcomes.